Mesurer l’impact scolaire des dispositifs d’enseignement artistique et culturel dans les établissements d’éducation prioritaire. Le cas du dispositif DMEO - Philippe Coulangeon; Héloïse Fradkine (Cahiers de la Recherche sur l'Education et les Savoirs)
This article relates to the evaluation of the academic impact of an artistic and cultural education program, ("Dix mois d’école et d’Opéra" - DMEO) carried out by the Paris Opera and the regional education authorities in Paris, Créteil and Versailles since the beginning of the 1990s. This program is aimed more particularly at middle school classes located in disadvantaged neighbourhoods. The article first describes the history and characteristics the program. It then developed an analysis of the school careers of students in about 50 middle schools classes involved in the program between 2003 and 2012 using a counterfactual method. These data relate to students scores at the final exam of middle school and end-of-year orientation choices, for which the results of the analysis suggest a modest but significant impact of participation in DMEO. These results also display a differentiation of this impact by gender and social origin of students, with overall effects more pronounced among boys and students from working-class backgrounds. Finally, the article emphasizes the uncertain nature of these effects, which can be clarified by conducting a qualitative survey in parallel with statistical analyses. We suggest that these effects are probably due more to changes in the conditions under which pupils are supervised and motivated, to forms of involvement and coordination of teaching teams than to the acquisition of academic skills in the strict sense.